Kompetensi Profesional: Strategi Guru dalam Mengelola Keberagaman Siswa di Sekolah Multikultural - Maulana, Atto'; Abdurrouf, Ishaq; Habib, Jidan Nur; Wulandari, Rizqi Melani (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze professional competence in managing student diversity in multicultural schools as well as examine learning strategies and cultural support as well as school policies in supporting multicultural educational practices. This study employs a qualitative approach, specifically a case study research design, conducted at SMP Negeri 1 Mertoyudan, Magelang Regency, which has a diverse student population in terms of religion, ethnicity, and academic ability. Data collection was carried out through observations, semi-structured interviews with principals, teachers, and students, and school policy documentation. The results of the study show that professional competence is reflected through an inclusive attitude, social sensitivity, and ethical commitment in safeguarding the learning rights of all students, including minority groups. Teachers apply inclusive learning strategies, such as active tolerance, heterogeneous group work, and differentiated learning, to accommodate differences in academic ability. A harmonious and conflict-free school culture also supports multicultural practices, although there are still structural obstacles in the fulfillment of religious education for minority students due to limited educators. This study concludes that professional competence and inclusive pedagogic strategies play an important role in maintaining harmony and quality of learning in multicultural schools with more affirmative and sustainable education policies.